Exploring Cultural Representation in Contemporary Works of Art - Syafira, Yumni (Professorline, 2024)
Cultural representation in contemporary art is becoming increasingly important in a diverse and interconnected society. This research explores how artists represent and negotiate their cultural identity through works of art. By using a qualitative approach, including content analysis, in-depth interviews, participant observation, and literature study, this research reveals the strategies, challenges, and impacts of cultural representation practices in contemporary art. The findings show that artists use various strategies such as symbol appropriation, personal narratives, as well as cultural criticism and intervention in their works. However, issues such as authenticity, cultural appropriation, stereotypes, and commodification are often challenges faced. On the other hand, cultural representation in art has positive impacts, such as building cross-cultural dialogue, empowering marginalized voices, and enriching the artistic landscape as a whole. This research highlights the role of contemporary art as a vehicle for negotiating cultural identity, exploring diversity, and advancing understanding and appreciation of cultural differences in global society.